Linkage of living microbial biomass, function, and necromass to soil organic carbon storage along a chronosequence of Larix principis-rupprechtii plantation in North China - Yang, Mengyun; He, Xiaomeng; Liang, Jingfei; Liu, Qiang; Fu, Lihua; Cui, Xiaodong; Huang, Shaohui; Luan, Haoan (Frontiers in Microbiology, 2025)
IntroductionClarifying the temporal dynamics of soil organic carbon (SOC) characteristics within aggregates and its underlying microbially mediated mechanisms is essential for long-term SOC sequestration in forest ecosystems; nevertheless, this information remains largely unknown during stand development.MethodsFive Larix principis-rupprechtii plantations of different ages (7a, 18a, 25a, 34a, and 44a) at the Saihanba Mechanical Forest Farm were chosen to elucidate the temporal variations in SOC characteristics and microbial attributes within aggregates (>2 mm, 2−0.25 mm, and <0.25 mm) following reforestation, based on 13C NMR, phospholipid fatty acid (PLFAs) analysis, micro-plate enzyme technique, and amino sugar analysis, etc.ResultsResults demonstrated that as stand ages increased, aggregate stability as well as aggregate-associated SOC, microbial residue C (MRC), hydrolytic exo-enzymatic activities, and microbial biomass (as indicated by total PLFAs) initially increased and subsequently decreased, with most parameters peaking in the 18a stand, which indicated that long-term Larix principis-rupprechtii plantations (>25a) were not favorable for promoting microbial growth, hydrolytic functions, and microbial metabolism. Besides, regardless of the stand age, the above-mentioned indices were generally higher in larger aggregates (>2 mm and 2−0.25 mm) compared to smaller aggregates (<0.25 mm). Notably, the increased stand ages (i.e., 34a and 44a) or decreased aggregate sizes (<0.25 mm) enhanced SOC stability (as indicated by the recalcitrance index) and oxidative exo-enzymatic activities, as well as enlarged MRC (especially fungal residue C) contribution to SOC. The partial least squares path model highlighted that SOC stocks were primarily regulated by MRC, while the microbial community altered SOC stability by modulating exo-enzyme activities.DiscussionThese results offered novel insights into elucidating the coupling connections between microbial attributes and SOC sequestration during forest development in northern China.